The NANOGrav 12.5 yr Data Set: Observations and Narrowband Timing of 47 Millisecond Pulsars - Alam, Md F.; Arzoumanian, Zaven; Baker, Paul T.; Blumer, Harsha; Bohler, Keith E.; Brazier, Adam; Brook, Paul R.; Burke-Spolaor, Sarah; Caballero, Keeisi; Camuccio, Richard S.; Chamberlain, Rachel L.; Chatterjee, Shami; et al. (The Astrophysical journal. Supplement series, 2021)
We present time-of-arrival (TOA) measurements and timing models of 47 millisecond pulsars observed from 2004 to 2017 at the Arecibo Observatory and the Green Bank Telescope by the North American Nanohertz Observatory for Gravitational Waves (NANOGrav). The observing cadence was three to four weeks for most pulsars over most of this time span, with weekly observations of six sources. These data were collected for use in low-frequency gravitational wave searches and for other astrophysical purposes. We detail our observational methods and present a set of TOA measurements, based on "narrowband" analysis, in which many TOAs are calculated within narrow radio-frequency bands for data collected simultaneously across a wide bandwidth. A separate set of "wideband" TOAs will be presented in a companion paper. We detail a number of methodological changes, compared to our previous work, which yield a cleaner and more uniformly processed data set. Our timing models include several new astrometric and binary pulsar measurements, including previously unpublished values for the parallaxes of PSRs J1832−0836 and J2322+2057, the secular derivatives of the projected semimajor orbital axes of PSRs J0613−0200 and J2229+2643, and the first detection of the Shapiro delay in PSR J2145−0750. We report detectable levels of red noise in the time series for 14 pulsars. As a check on timing model reliability, we investigate the stability of astrometric parameters across data sets of different lengths. We also report flux density measurements for all pulsars observed. Searches for stochastic and continuous gravitational waves using these data will be subjects of forthcoming publications.